Simulation of wear map for biodiesel interacted automotive materials - Cetin, S Y; Maleque, Md. Abdul; Masjuki, H H (IOP Publishing, 2022)
Selection of material for automotive component has an important role to avoid wear problem that encountered in static and moving parts due to fuels used in the engine especially, biodiesel. Biodiesel compositions such as dissolved water, free water and emulsified water accelerate oxidation of metallic materials. During the combustion process, the biodiesel contributes to the corrosive wear of the engine components leading to the shortening of the life span. The early prediction of the wear behavior under severe conditions in presence of biodiesel would be a vital solution. Therefore, the main aim of this study is to propose a wear map simulation for examining wear phenomenon of automotive component materials in presence of biodiesel. Herewith, materials that come into contact with biofuel/biodiesel in automotive application are highlighted for better design and selection in the future. This study concluded that based on the wear map simulation proper selection of material with higher durability and wear resistant can offer a better future for economic and reliability of the components. The development of wear map with recommendation aids researchers making decisions and innovation on the metals engine components. Furthermore, a full explanation on the reaction between biodiesel and metals can increase the innovation in the automotive industry. Keywords: wear, biodiesel, automotive materials, wear model